Mesterek és tanítványok. Különös tekintettel Kovács Albert hatására a 20. század eleji kolozsvári homiletika-oktatásra - KULCSÁR, Árpád (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2022)
Masters and Disciples. With Particular Focus on Albert Kovács’s Influence upon the Teaching of Homiletics in the Early 20th Century in Kolozsvár/Cluj-Napoca. In this paper, I examine the influence of Albert Kovács (1838–1904), Professor of Practical Theology between 1865 and 1904 at the Theological Seminary in Budapest, upon the teaching of homiletics in the early 20th century in Kolozsvár. After the sudden death of Albert Molnár (1849–1901), Lecturer of Practical Theology at the Theological Seminary in Kolozsvár (1895–1901), Béla Kenessey (1858–1918) continued his work (1901–1907). As former disciple of Albert Kovács, Kenessey used his personal notes from Kovács’s lectures. László Ravasz (1882–1975), Professor of Practical Theology (1907–1921), as the disciple of Kenessey in Kolozsvár, was directly influenced by Albert Kovács’s homiletical thoughts. In this paper, I attempt to demonstrate the influence of Albert Kovács by identifying Kenessey’s homiletical notes (1902) in the Manuscript Collection of the Theological Institute in Kolozsvár, by using an early (1909), handwritten version of László Ravasz’s homiletical handbook (1915) from the inheritance of his disciple Sándor Tavaszy (1888–1952). I also examine the value of László Ravasz’s thoughts in the context of the history of Hungarian and European Protestant homiletics and preaching.